1992
DOI: 10.1288/00005537-199206000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Drill‐generated sensorineural hearing loss following mastoid surgery

Abstract: Drilling during mastoid surgery may result in temporary noise-induced hearing loss. This has practical implications for both the patient and surgeon. In a prospective study of 40 patients, audiometric testing was done both preoperatively and postoperatively to try to detect any significant hearing loss in the immediate postoperative period. The data were analyzed using the Student's paired t test. No statistically significant difference was found. A sensorineural hearing loss soon after mastoid surgery is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0
3

Year Published

1997
1997
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 13 publications
0
56
0
3
Order By: Relevance
“…This has practical implications for both the patient and the surgeon. 7 Noise exposure results in dysfunction of the outer hair cells, which may produce a temporary hearing loss on surgery applied or other ears. 8 Tympanoplasty can also cause a SNHL by a mechanism of acoustic trauma.…”
Section: Introductionmentioning
confidence: 99%
“…This has practical implications for both the patient and the surgeon. 7 Noise exposure results in dysfunction of the outer hair cells, which may produce a temporary hearing loss on surgery applied or other ears. 8 Tympanoplasty can also cause a SNHL by a mechanism of acoustic trauma.…”
Section: Introductionmentioning
confidence: 99%
“…The expected hearing loss may be missed if pure tone audiometry is utilized [3,4] . Although Da Cruz et al [5] reported drill-induced contralateral temporary hearing loss by changes in amplitudes of distortion product OAEs (DPOAEs), longitudinal recovery of this temporary hearing loss has not been studied before.…”
Section: Introductionmentioning
confidence: 99%
“…Urquhart et al (12) reported in their study that they did not find early hearing loss associated with vibration after drilling, but they stated that long-term effects of drilling were unknown. In this study conducted in 1992, standard audiometric analysis was performed to test hearing.…”
Section: Discussionmentioning
confidence: 98%